Differential expression of genes related to glucose metabolism in domesticated pigs and wild boar. Issue 8 (3rd August 2017) - He, Dafang; Ma, Jideng; Long, Keren; Wang, Xun; Li, Xuewei; Jiang, Anan; Li, Mingzhou
Abstract: Glucose metabolism is a basic biological process that shows substantial variation within and between species. Using pig as a model organism, we investigated differences in glucose metabolic genes in seven tissues from domesticated pigs (Rongchang pig and Tibetan pig, meanwhile, the Tibetan pig just as a special case of the domesticated pig under plateau condition) and wild boar. We found large differences in the expression of genes involved in multiple aspects of glucose metabolism, including genes associated with glucose transport, gluconeogenesis, and glycolysis. In addition, we identified microRNAs (miRNAs) that may be involved in the divergence of glucose metabolism in pig. A combined analysis of mRNA and miRNA expression indicated that some miRNA:mRNA pairs showed ab facto function in it. Our results provide a valuable resource for further determination of miRNA regulatory roles in pig glucose metabolism and reveal the divergence of glucose metabolism in pigs under domestication. Abstract : :